DETERMINATION OF RETENTION INDICES OF ISOPROPYL OLEATE, ISOBUTYL OLEATE, AND DIETHYL-HEXYL PHTHALATE BY USING GAS CHROMATOGRAPHY/MASS SPECTROMETRY - Pusfitasari, Eka Dian; Andreas, - (Teknologi Indonesia, 2013)
Diethyl-hexyl phthalate (DEHP) is the most commonly use of phthalate in plastic packed. There were several cases which subtituted the composition of DEHP in the plastic packed with vegetable oil derivative, such asIsopropyl oleate and Isobutyl oleate from palm oil, because DEHP have negative effect for health. Although it has been substituted with the Isopropyl oleate (IPO) and Isobutyl oleate (IBO), to a certain degree, the DEHP could be evaporated from the foil to its surrounding. Therefore, the analysis of both IPO and IBO is very important to be done. Analysis of IPO, IBO, and DEHP were done using GC equipment with DB-5 column and MS detector. Identifi cation by using Kovats Retention Indices (RI) values is believed to provide optimal results in qualitative analysis, since each compound has a different RI value. Determination of RI value of IPO, IBO and DEHP in various parameters using GC-MS instrument at several ramp temperature conditions of GCs column was done. Meanwhile, the variation of temperature and fl ow rate of carrier gas also became parameter to reach different RT to calculate RI. Determination of the retention indices of IPO, IBO, and DEHP showed that RI laid in the near value range. The RIvalues of those three compounds are 2194, 2317, and 2534, respectively. The different retention time of a certain compounds as a result of a shift or changes of testing parameters will not infl uence the value of its retention indices.